A double-layer smart charging strategy of electric vehicles taking routing and charge scheduling into account - Yagcitekin, Bunyamin; Uzunoglu, Mehmet (ELSEVIER SCI LTD, 2016)
This paper presents a double-layer smart charging management algorithm (SCMA) for electric vehicles in working place parking lots considering smart grid concept. This model enables safe and controlled charging, which satisfies both power grid and drivers' needs comprehensively. First level of SCMA controls each transformer power demand, transformer capacity, charging station status and the shortest way to reach suitable charger. Second level of SCMA is used during the charging process in order to provide cost-effective and reliable charging as well as less impact on power grid. The proposed SCMA strategy successfully routes the electric vehicles (EVs) to the most suitable charging point, decreases the charging costs and prevents the overloading of transformers. In this study, a comparison regarding the impacts of the whole charging process of the EVs on the power grid and drivers' requests with/without the proposed SCMA is presented and the results are discussed in detail. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Electric vehicle; Smart charging; Energy management; Daytime charging; Optimization; Distribution network; HOME ENERGY MANAGEMENT; FUEL CONSUMPTION; DEMAND; MODEL; Energy & Fuels; Engineering